Thermophile Lytic Enzyme Fusion Proteins that Target Clostridium perfringens - Steven M. Swift; Kevin P. Reid; David M. Donovan; Timothy G. Ramsay (MDPI AG, 2019)
Clostridium perfringens is a bacterial pathogen that causes necrotic enteritis in poultry and livestock, and is a source of food poisoning and gas gangrene in humans. As the agriculture industry eliminates the use of antibiotics in animal feed, alternatives to antibiotics will be needed. Bacteriophage endolysins are enzymes used by the virus to burst their bacterial host, releasing bacteriophage particles. This type of enzyme represents a potential replacement for antibiotics controlling C. perfringens. As animal feed is often heat-treated during production of feed pellets, thermostable enzymes would be preferred for use in feed. To create thermostable endolysins that target C. perfringens, thermophile endolysin catalytic domains were fused to cell wall binding domains from different C. perfringens prophage endolysins. Three thermostable catalytic domains were used, two from prophage endolysins from two Geobacillus strains, and a third endolysin from the deep-sea thermophilic bacteriophage Geobacillus virus E2 (GVE2). These domains harbor predicted L-alanine-amidase, glucosaminidase, and L-alanine-amidase activities, respectively and degrade the peptidoglycan of the bacterial cell wall. The cell wall binding domains were from C. perfringens prophage endolysins (Phage LYtic enzymes; Ply): PlyCP18, PlyCP10, PlyCP33, PlyCP41, and PlyCP26F. The resulting fifteen chimeric proteins were more thermostable than the native C. perfringens endolysins, and killed swine and poultry disease-associated strains of C. perfringens.